Moderating Effect of Inflation Risk on the Effect of Profitability, Managerial Ownership on Stock Returns and Debt as Moderating Variables - Hanny Stevany; Rudolf Lumban Tobing; Lambok DR Tampubolon (Fakultas Bisnis, 2022)
The main goal of investors in investing in the capital market, especially the stock market, of course, investors want a high level of return with minimal risk. Therefore, an investor needs information to analyze the fundamentals of a company using the company's financial data. This study uses inflation risk variables as a moderating effect, profitability and managerial ownership as independent variables, and debt as a mediating variable. The data used is secondary data using 20 manufacturing companies in the consumer good industry sector listed on the Indonesia Stock Exchange in the 2016-2019 period with 80 samples used. In processing the data, the programs used are SPSS version 24 and the Sobel Test Online Calculator. Based on the coefficient of determination test, the value of R2 indicates that the dependent variable can be explained by 12.8% by the independent variable. Based on the results of the F test, all dependent variables have an influence on the independent variables. However, the results of the t test show that only profitability and managerial ownership have a positive and significant effect on stock returns, while debt has no significant effect on stock returns. The results of the t-test also show that profitability and managerial ownership have a strengthening effect on stock returns with debt as a mediating variable. Meanwhile, the moderating effect of inflation risk on the effect of profitability and managerial ownership also shows a strong and significant result on stock returns.